Book Review – 2020. Issue 1 (10th August 2020) - Douce, Chris; Chtena, Natascha; Ferguson, Gillian; Fox, Alison; Gray, Brenna Clarke
The following publication contains book reviews of these titles: - Herodotou, C., Sharples, M. and Scanlon, E. (eds) (2018 ) Citizen Inquiry: Synthesising Science and Enquiry Learning . London: Routledge, 237 pages ISBN 9781138208698 - Baxter, J., Callaghan, G., and McAvoy, J. (eds) (2018 ) Creativity and Critique in Online Learning: Exploring and Examining Innovations in Online Pedagogy . London: Palgrave Macmillan, 287 pages ISBN 978-3-030-08668-8 - Krause, S.D. (2019 ) More than a Moment, Contextualizing the past, present, and future of MOOCS, Utah: Utah State University Press. 168 pages. ISBN: 9781607327868 (paperback) 9781607327875 (ebook) - Rowell, C. (ed) (2019 ) Social Media in Higher Education: Case Studies, Reflections and Analysis, Cambridge, UK: OpenBook Publishers 304 pages ISBN 9781783746682. Available as an open access book at:https://doi.org/10.11647/OBP.0162 - Morris, S. M. & Stommel, J. (2019 ), An Urgency of Teachers: The Work of Critical Digital Pedagogy . Hybrid Pedagogy, Open Access:https://criticaldigitalpedagogy.pressbooks.com/ ISBN 9780692152690.